LOSS OF THE SEX-CHROMOSOME IN HUMAN NEOPLASIAS OF THE NERVOUS-SYSTEM - Rogatto, Silvia Regina [UNESP]; Rainho, C. A.; Neto, J. B.; Casartelli, C. (Soc Brasil Genetica, 1994)
Thirty-eight tumors (five grade I-II astrocytomas, three grade III astrocytomas, four glioblastomas, one oligodendroglioma, four ependymomas, one pineocytoma, three medulloblastomas, four acoustic nerve neurinomas, one intraspinal neurinoma, one neurofibroma, 10 meningiomas, and one craniopharyngioma) and three benign lesions of the nervous system were evaluated cytogenetically after in vitro culture. Sex chromosome loss was detected in 56% of the cases (-X in 13 of the 25 female patients and -Y in nine of the 16 male patients). The objective of the present report was to study the role of this abnormality in cells of the nervous system.